Ask a question

Answers by Callee B.

(a-9)(a+9)=0 (answer)

To solve this, you want to set each of the parentheses equal to 0 and then solve for the variable. a-9=0  To solve for a, add 9 to each side, making a=9. a+9=0 To solve for a here, subtract 9 from each side, making a=-9. The final answer is a=-9,9    

You first want to look at the values that make up the expression, 6y and 15. Obviously, you can't take a y out, because y is only in one of the values. Now, you compare 6 and 15. These have a common factor of 3, so you need to divide each by 3. You get a final answer of 3(2y+5)